Impact of goods and services tax and redistribution among households in Malaysia - Syeddin, Siti Nur'amalina (2020)
Goods and Services Tax (GST) is imposed on goods and services. It has been implemented in most of the 160 countries in the world. Taxes are part of the government revenues and Malaysia rely more on the direct taxes particularly on petroleum income tax. However, the volatility of the oil prices gives an impact on the government revenues. As a result, government introduce GST to cushion the impact of volatility of the decline in oil-related revenue as this consumption tax is positive for fiscal strength. Nevertheless, the main question is whether the GST has led to a price increment directly caused the cost of living to increase as well.